2021
DOI: 10.1371/journal.pmed.1003669
|View full text |Cite
|
Sign up to set email alerts
|

Pyronaridine–artesunate real-world safety, tolerability, and effectiveness in malaria patients in 5 African countries: A single-arm, open-label, cohort event monitoring study

Abstract: Background In Phase II/III randomized controlled clinical trials for the treatment of acute uncomplicated malaria, pyronaridine–artesunate demonstrated high efficacy and a safety profile consistent with that of comparators, except that asymptomatic, mainly mild-to-moderate transient increases in liver aminotransferases were reported for some patients. Hepatic safety, tolerability, and effectiveness have not been previously assessed under real-world conditions in Africa. Methods and findings This single-arm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 18 publications
10
33
0
Order By: Relevance
“…Our findings are consistent with previous studies and most frequently observed AEs were similar to these previous studies and malaria symptoms. 13,14,16,19,28 This study supports what has been observed with PA safety up until now.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are consistent with previous studies and most frequently observed AEs were similar to these previous studies and malaria symptoms. 13,14,16,19,28 This study supports what has been observed with PA safety up until now.…”
Section: Discussionsupporting
confidence: 89%
“…[13][14][15][16][17] The safety warning that was reported with the PA use was a transient increase of hepatic transaminases, 13,14,16,17 without any clinical signs or symptoms of hepatotoxicity. 13,18,19 Therefore, WHO recommends malaria-endemic countries to include PA in their national treatment guidelines. 12 However, this deployment should be conducted under a strong pharmacovigilance system as required for the introduction of all new medicines.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“… 23 However, the effects of antimalarials on the sexual stages of Plasmodium malariae and Plasmodium ovale spp, and the characteristics of those stages, have not been described conclusively so far. 12 , 24 Therefore, we cannot rule out that these submicroscopic parasitaemias were due to sexual stages of said non-falciparum parasite species that, to date, cannot be reliably distinguished from asexual stages with the available molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…We did a post-hoc analysis assessing samples collected during the CANTAM-Pyramax trial ( NCT03201770 ), which has been published in more detail elsewhere. 12 In short, the CANTAM-Pyramax trial was an open label, non-randomised, phase 3b/4, cohort event monitoring study designed to evaluate, in a real-life setting, the safety, tolerability, and efficacy of pyronaridine–artesunate therapy administered daily over 3 consecutive days in patients with uncomplicated malaria. Patients were included on the basis of a positive rapid diagnostic test (RDT) result or malaria microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation